Globalization And Increasing Domination Over The Nation State - Orhan, Ertuğrul Buğra (Fırat University, 2021)
Globalization is a phenomenon that deeply affects today's economies and politics. The excessive growth of global companies erodes the economic and political effectiveness of nation states. It is seen that this phenomenon is handled with different approaches in the context of globalization literature. However, especially the approach put forward by the critical theory has been the academic parameter adopted for this research. Therefore, the focus is on the context of the approach of globalization that strengthens capital companies and negatively affects nation states. In the research, it has been concluded that the nation state was the dominant actor of the global system, whereas today nation states are under pressure. In addition, it has been concluded that global capital companies are in a dominating position against nation states. The concepts of freedom, intervention, and domination have been abstract explanators in reaching this conclusion. The method adopted in the use of concepts is the functionality of the concepts and the related concepts approach. These approaches have been evaluated with an inductive conceptualization.

Globalization is a phenomenon that deeply affects today's economies and politics. The excessive growth of global companies erodes the economic and political effectiveness of nation states. It is seen that this phenomenon is handled with different approaches in the context of globalization literature. However, especially the approach put forward by the critical theory has been the academic parameter adopted for this research. Therefore, the focus is on the context of the approach of globalization that strengthens capital companies and negatively affects nation states. In the research, it has been concluded that the nation state was the dominant actor of the global system, whereas today nation states are under pressure. In addition, it has been concluded that global capital companies are in a dominating position against nation states. The concepts of freedom, intervention, and domination have been abstract explanators in reaching this conclusion. The method adopted in the use of concepts is the functionality of the concepts and the related concepts approach. These approaches have been evaluated with an inductive conceptualization.
GLOBALIZATION AND INCREASING DOMINATION OVER THE NATION STATE